Trimethylamine N-Oxide Exacerbates Renal Inflammation and Fibrosis in Rats With Diabetic Kidney Disease - Fang, Qing; Zheng, Binjie; Liu, Na; Liu, Jinfeng; Liu, Wenhui; Huang, Xinyi; Zeng, Xiangchang; Chen, Lulu; Li, Zhenyu; Ouyang, Dongsheng (Frontiers in Physiology, 2021)
The gut microbiota plays a pivotal role in the onset and development of diabetes and its complications. Trimethylamine N-oxide (TMAO), a gut microbiota-dependent metabolite of certain nutrients, is associated with type 2 diabetes and its complications. Diabetic kidney disease (DKD) is one of the most serious microvascular complications. However, whether TMAO accelerates the development of DKD remains unclear. We tested the hypothesis that TMAO accelerates the development of DKD. A high-fat diet/low-dose streptozotocin-induced diabetes rat model was established, with or without TMAO in the rats’ drinking water. Compared to the normal rats, the DKD rats showed significantly higher plasma TMAO levels at the end of the study. TMAO treatment not only exacerbated the kidney dysfunction of the DKD rats, but also renal fibrosis. Furthermore, TMAO treatment activated the nucleotide-binding domain, leucine-rich-containing family, pyrin domain-containing-3 (NLRP3) inflammasome and resulted in the release of interleukin (IL)-1β and IL-18 to accelerate renal inflammation. These results suggested that TMAO aggravated renal inflammation and fibrosis in the DKD rats, which provides a new perspective to understand the pathogenesis of DKD and a potential novel target for preventing the progression of DKD.